Experiment study on the cross-layer propagation characteristics of hydraulic fracturing cracks in coal roof rocks - Maolin Yang; Shuai Lv; Xing Wang; Mao Wang; Sicheng Wang; Yu Meng; Yongjiang Luo (PLoS ONE, 2025)
Fracture of the overlying roof of a coal seam has become the main method to increase the permeability of coal seam in coalbed methane exploitation. Because the fracture must grow into the coal and through any stone layers, the mechanical property difference between the overlying roof rocks and coal inevitably leads to significant changes in the crack propagation behaviors. In this study, an embedded strain sensor with low cost and simple operation is used to measure the strain in laboratory samples representing the coal seam and roof near the interface for fractures initiated in the roof to obtain the width change of the hydraulic fracture at the interface. At the same time, the propagation behavior of hydraulic fractures at the interface is expressed by combining fracture images and pumping pressure. The results show that a larger horizontal stress difference, larger flow rate, lower coal seam modulus, and smaller intermediate layer thickness are beneficial for the propagation of hydraulic fractures from the roof into the coal seam and the activation of the roof-coal interface. On-site hydraulic fracturing design should fully consider the in-situ stress and coal seam modulus, and design reasonable fracturing drilling location and injection flow. The width of hydraulic fracture in coal seam is larger than that in roof, and increases with the modulus of coal and roof approach, which is beneficial to the migration of proppant in roof-coal seam hydraulic fracture. Therefore, the migration of fracturing proppant in an actual coal seam roof is limited by the width of hydraulic fractures in the roof.